The Oxford handbook of behavioral economics and the law - Zamir, Eyal; Teichman, Doron (New York : Oxford University Press, 2014)
'The Oxford Handbook of Behavioral Economics and Law' brings together leading scholars of law, psychology, and economics to provide an up-to-date and comprehensive analysis of this field of research, including its strengths and limitations as well as a forecast of its future development. Its twenty-nine chapters are organized into four parts.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on October 30, 2014).
Keywords: Economics -- Psychological aspects -- Handbooks, manuals, etc; Law and economics -- Handbooks, manuals, etc